2017
DOI: 10.1038/s41598-017-01873-3
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and Self-Healing Aqueous Supercapacitors for Low Temperature Applications: Polyampholyte Gel Electrolytes with Biochar Electrodes

Abstract: A flexible and self-healing supercapacitor with high energy density in low temperature operation was fabricated using a combination of biochar-based composite electrodes and a polyampholyte hydrogel electrolyte. Polyampholytes, a novel class of tough hydrogel, provide self-healing ability and mechanical flexibility, as well as low temperature operation for the aqueous electrolyte. Biochar is a carbon material produced from the low-temperature pyrolysis of biological wastes; the incorporation of reduced graphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(61 citation statements)
references
References 54 publications
(58 reference statements)
2
55
0
Order By: Relevance
“…Here, microscopic cellular structures were observed in the DIW-dialyzed sample, whereas there is no visible macroscopic structure in the KOH-dialyzed sample. This morphologic observation is consistent with high mechanical strength [21,22] and high low-temperature ionic conductivity, [16,20] respectively, reported in previous literatures.…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…Here, microscopic cellular structures were observed in the DIW-dialyzed sample, whereas there is no visible macroscopic structure in the KOH-dialyzed sample. This morphologic observation is consistent with high mechanical strength [21,22] and high low-temperature ionic conductivity, [16,20] respectively, reported in previous literatures.…”
Section: Introductionsupporting
confidence: 92%
“…[14] Moreover, the upper critical solution temperature of polyampholyte hydrogel can be manipulated by tuning the strength of ionic interactions. [15] Based on these unique properties of ionic cross-linking, polyampholyte hydrogels have been used as electrolyte for flexible and selfhealing supercapacitors, [16] and as an optically modulating substance for thermosensitive smart windows. [17] Such diverse applications of polyampholyte hydrogels are possible by controlling morphology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the process of low‐rate charge and discharge, ionic electrolyte is easier to transfer in the pores with large sizes, making full use of the surface area of carbon . A certain amount of mesopores and macropores can be necessary for the rapid diffusion of electrolyte ions, which not only can effectively improve the accessibility of micropores, also serve as a channel for rapid diffusion of ions, promoting the rapid transport of electrolyte ions, thereby greatly improving electrochemical performance of SCs . Mi et al observed the equivalent series resistance decreased with the increase of V meso / V total of the porous carbons, which led to a high capacitance.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…87 A certain amount of mesopores and macropores can be necessary for the rapid diffusion of electrolyte ions, which not only can effectively improve the accessibility of micropores, also serve as a channel for rapid diffusion of ions, promoting the rapid transport of electrolyte ions, thereby greatly improving electrochemical performance of SCs. 159,160 Mi et al 34 observed the equivalent series resistance decreased with the increase of V meso /V total of the porous carbons, which led to a high capacitance. HPCs have a higher specific capacitance and capacity retention ratio at a large current density than the porous carbon having a single microporous structure.…”
mentioning
confidence: 99%